Innovation Strategy and Product Development to Increase Company Competitiveness in Digital Era - Sayudin Sayudin; Aisyah Nurjanah; Aldian Yusup (Eduvest - Journal of Universal Studies, 2023)
The development of technology and digitalization affects various aspects of life, including in the business world. Competition in the business world is getting tighter, so the right product innovation and development strategy is needed to improve the company's competitiveness. Therefore, this research was conducted to understand product innovation and development strategies that can help improve the competitiveness of companies in the digital era. The purpose of this research is to analyze product innovation and development strategies that can improve the competitiveness of companies in the digital era. This research uses a qualitative approach. Data was collected through documentation studies. The data was then analyzed descriptively with content analysis techniques. The results showed that product innovation and development strategies carried out by companies in the digital era include the use of information and communication technology, product research and development, collaboration with other parties, and product diversification. These product innovation and development strategies are considered effective in increasing the company's competitiveness in the digital era